Biological preservation of mayonnaise with Lactobacillus plantarum LBRZ12, dill, and basil essential oils. (15th May 2021) - Teneva, Desislava; Denkova, Zapryana; Denkova-Kostova, Rositsa; Goranov, Bogdan; Kostov, Georgi; Slavchev, Aleksandar; Hristova-Ivanova, Yana; Uzunova, Galina; Degraeve, Pascal
Highlights: Mayonnaise was preserved by dill and basil essential oils, and L. plantarum. Dill and basil essential oils exhibited potent antimicrobial activity. Undesired microflora in mayonnaise was suppressed by essential oils and L. plantarum. L. plantarum, dill and basil oils could serve as bio preservative agents in foods. Abstract: In this study, different variants of egg-free mayonnaise containing free and immobilized Lactobacillus plantarum LBRZ12 cells and essential oils taken from basil and dill were prepared. The composition and antimicrobial properties of essential oils were investigated. The main constituents of basil oil were methyl chavicol (36.81%), methyl eugenol (20.40%), β -linanool (14.35%), eugenol (10.55%), and L(-)-carvone (39.05%), whereas dill oil contained mostly d -limonene (21.11%) and α -phellandrene (22.68%). The essential oils exhibited strong antimicrobial activity against all test-microorganisms. The mayonnaise variants were kept refrigerated for 40 days and changes in pH, concentration of viable cells of lactobacilli, microbiological, and organoleptic characteristics were monitored. The pH decreased from 6.5 to 4.5 over the period of storage. The number of undesired microflora in mayonnaise preserved with lactobacilli and essential oils decreased significantly (0 after the 20th day) indicating their effectiveness as biological preservatives. The mayonnaise variants demonstrated pleasant organoleptic characteristics, thus meet customers' requirements.